Strategi Public Relations BTS dalam Meraih Kesuksesan Global dan Relevansinya terhadap Sustainable Development Goals (SDGs) 8 Dan 9 - Andhini Winariyanti (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
The remarkable global ascent of BTS, a South Korean music group operating under HYBE Corporation (formerly Big Hit Entertainment), is inseparable from a well-orchestrated and adaptive public relations (PR) framework. This study examines how HYBE's PR strategies propelled BTS to international prominence while simultaneously aligning with the Sustainable Development Goals (SDGs), specifically SDG 8 (Decent Work and Economic Growth) and SDG 9 (Industry, Innovation, and Infrastructure). Adopting a qualitative methodology grounded in media content analysis, the research draws on data from international and national news coverage, official press materials, public speeches, digital platform content, and institutional documents spanning 2017 to 2024. Four strategic pillars characterize BTS's PR approach: (1) sustained authentic narrative construction centered on personal growth, social responsibility, and cultural pride; (2) strategic mobilization of the global ARMY fanbase as an active communication force; (3) integrated and innovative utilization of digital media ecosystems to amplify reach and engagement; and (4) deliberate repositioning of BTS as contributors to economic and industrial transformation through creative industries. The findings demonstrate that BTS's PR model does not merely serve commercial objectives; rather, it operates as a mechanism for advancing inclusive economic growth and fostering innovation within the global creative sector. This research contributes to the theoretical discourse on PR's evolving role at the intersection of popular culture, digital innovation, and global sustainable development.